The immunotherapy advancement targeting malignant blastomas in early childhood - Zang, Bolun; Ding, Luyue; Liu, Linlin; Arun Kumar, Senthil; Liu, Wei; Zhou, Chongchen; Duan, Yongtao (Frontiers in Oncology, 2023)
Malignant blastomas develop chronologically in all functional body organs inflicting severe health ailments in younger children. Malignant blastomas exhibit diverse clinical characteristics in compliance with their emergence in the functional body organs. Surprisingly, neither of these preferred treatment types: surgery nor radiotherapy, and chemotherapy witnessed promising or effective to treat malignant blastomas among younger child patients. In recent times, the invention of innovative immunotherapeutic procedures encompassing monoclonal antibodies, and chimeric-antigen based receptor (CAR) cell therapy coupled with the clinical exploration of reliable therapeutic targets and immune regulatory pathways targeting malignant blastomas, procures wide attention amongst the clinicians of this era.